Verruciform xanthoma associated with lichen planus - Cristianne Kalinne Santos Medeiros; Glória Maria de França; Weslay Rodrigues da Silva; Joaquim Felipe Júnior; Hébel Cavalcanti Galvão; Patrícia Teixeira de Oliveira (University of São Paulo, 2022)
Verruciform xanthoma (VX) is a rare benign lesion of unknown etiology, with a rough or papillary aspect, painless, sessile, well-defined, most lesions do not exceed 2 cm in their largest diameter, the degree of keratinization of the surface influences color, varying white to red, affecting mainly the gingiva and alveolar mucosa, and can also be seen in skin and genital. Herein, we present a report a clinical case of oral verruciform xanthoma in the buccal mucosa associated with the lichen planus lesion, as well as the morphological and immunohistochemical characteristics of the lesion. The clinical diagnostic hypothesis of oral lichen planus of the white reticular lesions on the buccal mucosa and on the tongue was confirmed by histopathology before a subepithelial connective tissue exhibiting intense inflammatory infiltrate in a predominantly lymphocytic band. In contrast, the hypothesis of the verrucous lesion in the left buccal mucosa was leukoplakia, with histopathological evidence showing exophytic and digitiform proliferations with parakeratin plugs between the papillary projections. Subepithelial connective tissue was characterized by macrophages with foamy cytoplasm (xanthoma cells). An immunohistochemical examination was performed, showing positivity for CD68, a macrophage marker, in addition to testing by Schiff's periodic acid (PAS) with diastasis, which was detected the presence of lipids inside these macrophages. The patient is free of recurrences of verruciform xanthoma and is being monitored due to the presence of lesions of oral lichen planus.